Pengaruh Kebiasaan Belajar dan Sikap Siswa Terhadap Hasil Belajar Matematika - Eleonora Dwi w; Lydia Arfani Suangga; Ibnu Sina (Universitas Pancasakti Tegal, 2021)
This study aims to describe the influence of students' learning habits and attitudes in the mathematics learningprocess. The purpose of this study was to prove how the influence of students' learning habits and attitudes onmathematics learning outcomes. This study uses a quantitative approach with the Expos t facto method. Datacollection techniques used are interviews, documentation, and questionnaires. To find out the results of learningmathematics and questionnaires using a Likert scale 4 for data on students' learning habits and attitudes. Theresearch data were then analyzed using simple regression and multiple regression. The results showed that therewas an influence between study habits and students' attitudes towards mathematics learning outcomes.